Fiber-grade multi-element synergistic flame-retardant polyamide 6 and preparation method thereof

By adopting the melt blending technology of multivariate synergistic flame retardant powder and polyamide 6 pellets, fiber-grade multivariate synergistic flame retardant polyamide 6 is produced, which solves the problems of flame retardant in the prior art that have a great impact on physical properties, poor smoke resistance and complex preparation, and achieves efficient flame retardant, smoke inhibition and simplified preparation processes.

CN119735946APending Publication Date: 2025-04-01ZHEJIANG UNIV OF TECH SHENGZHOU INNOVATION RES INST CO LTD +1

Patent Information

Application Number
CN202510037118.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the flame retardant has a great impact on the physical properties of polyamide 6, poor smoke suppression, complex preparation process, and high requirements for equipment.

Method used

The multivariate synergistic flame retardant powder, including the organic phosphorus-silicon system flame retardant, dialuminum hypophosphorate and lanthanum oxide powder, was extruded, cooled, pelletized and dried with polyamide 6 pelletized through melt blending technology to obtain fiber-grade multivariate synergistic flame retardant polyamide 6.

Benefits of technology

The high limit oxygen index, low heat release rate and significant smoke suppression effect of polyamide 6 are achieved, reducing mechanical losses, simplifying the preparation process, reducing equipment requirements, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235841290000031
    Figure BDA0005235841290000031
  • Figure BDA0005235841290000035
    Figure BDA0005235841290000035
  • Figure BDA0005235841290000041
    Figure BDA0005235841290000041
Patent Text Reader

Abstract

The invention provides fiber-grade multi-element synergistic flame-retardant polyamide 6 and a preparation method thereof, and belongs to the technical field of flame-retardant polyamide 6. The multi-element synergistic flame retardant composite material is prepared from the following raw material components in parts by weight: 9.3 to 14 parts of multi-element synergistic flame retardant powder and 86.3 to 90.7 parts of polyamide 6 cut particles, the multi-element synergistic flame retardant powder comprises an organic phosphorus-silicon system flame retardant, dialuminum hypophosphite and lanthanum oxide powder. The limit oxygen index of the prepared fiber-grade multi-element synergistic flame-retardant polyamide 6 can reach 34% or above, the heat release rate is reduced by 45% or above, the total heat release amount is 12 MJ / m < 2 >, the peak value of the smoke generation rate is 0.08 m < 2 > / s, the smoke density is reduced to 20, molten drops are not generated, the mechanical loss is smaller than 10%, and the fiber-grade multi-element synergistic flame-retardant polyamide 6 has good smoke suppression performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of flame-retardant polyamide 6, and in particular to a fiber-grade multi-component synergistic flame-retardant polyamide 6 and a preparation method thereof. Background Art

[0002] As one of the earliest synthetic fibers to achieve industrial production, polyamide 6 fiber has been widely used in all aspects of national production and daily life due to its excellent physical and chemical properties. However, the flammability and serious droplet problem of polyamide 6 fiber greatly limit its application in certain professional fields. Therefore, the flame retardant modification of polyamide 6 fiber has received great attention from experts and scholars at home and abroad. So far, various types of flame retardants have been developed in the research field of flame retardant nylon 6 fiber, including halogens, nitrogen, phosphorus, silicon and nanomaterials. However, further research found that the toxicity of the combustion products cannot meet the ever-increasing halogen-free environmental protection requirements, the smoke and droplet phenomena generated by combustion, the great influence on the comprehensive properties of the fiber, and the lack of durability of the flame retardant effect. Therefore, the development of a flame retardant polyamide 6 pellet with good flame retardant properties, smoke suppression and anti-droplet has become a current technical challenge and demand.

[0003] At present, halogen flame retardants still dominate the field of flame-retardant polyamide 6 pelletizing and its preparation. Although halogen flame retardants can effectively achieve gas phase flame retardancy, they will release a large amount of toxic byproducts during the combustion process, causing serious environmental pollution and posing a threat to personal safety. In reference 1 (Cheng Baofa, Ma Tenghao, Li Xiangmei, et al. Flame retardant properties of polyamide 6 / diethylaluminum hypophosphite composites [J]. Synthetic Resins and Plastics, 2016, 33 (4): 24-28.), diethylaluminum hypophosphite (ADP) and polyamide 6 (PA6) were melt-blended by a twin-screw extruder, and the obtained PA6 / ADP composite was studied by differential scanning calorimeter, vertical combustion tester, limiting oxygen index instrument and cone calorimeter. The thermal properties, mechanical properties and combustion properties of the composite material were studied. The results show that the addition of ADP increases the glass transition temperature of PA6 / ADP composites; although the addition of ADP slightly reduces the mechanical properties of PA6, when w(ADP) is 22%, the limiting oxygen index of PA6 increases from 26.7% to 33.5%, and the vertical combustion level (1.6mm sample thickness) increases from V-2 to V-0, without melt dripping. In addition, the peak heat release rate increases from 1200kW / m 2 Reduced to 500kW / m 2 The dense carbon layer formed by the composite material after combustion effectively blocks the transfer of radiant heat and oxygen to the PA6 matrix.

[0004] Reference 2 (Chen Guancong. Research on New Expanded Halogen-free Flame Retardant HDPE [D], 2011) The addition of rare earth lanthanum oxide (LaO) can improve the thermal stability of HDPE in nitrogen and air atmospheres. Taking LaO and IFR synergistic flame retardant HDPE as an example, when the LaO dosage is 1%, the synergistic flame retardant effect is the best, the LOI of HDPE / IFR / LaO composite material is 32.3, and the vertical combustion reaches UL-94 V-0 level. LaO can improve the thermal stability of the flame retardant system, promote the formation of a stronger and denser carbon layer when the flame retardant system burns, and can improve the OIT of the flame retardant material. Based on this, it is thought that nano lanthanum oxide can react with polyamide 6 to improve the stability of the flame retardant system and produce a smoke suppression effect. For example, the patent with application number 201911012243.6 discloses a Schiff base PN-Si flame retardant polyamide 6, fiber and preparation method thereof. The PN-Si flame retardant introduced in the patent has the characteristics of halogen-free, environmentally friendly, excellent thermal stability, high residual carbon rate, excellent water resistance and good compatibility with PA6 substrate. After the PN-Si flame retardant is melt-blended with polyamide 6, the flame retardant polyamide 6 obtained exhibits the advantages of halogen-free, no droplets, high flame retardant efficiency and low heat release. However, the flame retardant still has some shortcomings, such as a large impact on the physical properties of polyamide 6, poor spinnability, complex preparation process, inability to effectively suppress smoke and high equipment requirements.

[0005] Therefore, there is an urgent need for a fiber-grade multi-component synergistic flame-retardant polyamide 6 that improves flame retardancy and spinnability and reduces mechanical loss and smoke generation. Summary of the invention

[0006] The purpose of the present invention is to provide a fiber-grade multi-component synergistic flame-retardant polyamide 6 and a preparation method thereof, so as to solve the technical problems in the prior art that flame retardants have a great influence on the physical properties of polyamide 6, smoke suppression is poor, the preparation process is complicated, and the equipment requirements are high.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a fiber-grade multi-component synergistic flame-retardant polyamide 6, which is prepared from raw materials comprising the following parts by weight:

[0009] 9.3-14 parts of multi-component synergistic flame retardant powder;

[0010] Polyamide 6 pellets 86-90.7 parts;

[0011] The multi-component synergistic flame retardant powder comprises an organic phosphorus-silicon system flame retardant, dialuminum hypophosphite and lanthanum oxide powder.

[0012] Furthermore, the mass ratio of the organic phosphorus-silicon system flame retardant, dialuminum hypophosphite and lanthanum oxide powder is 1-5:8:0.3-1.

[0013] Furthermore, the structural formula of the organic phosphorus-silicon system flame retardant is:

[0014]

[0015] Among them, R1 is R2 is R3 is

[0016] Furthermore, the preparation method of the organic phosphorus-silicon system flame retardant comprises the following steps:

[0017] 200 mL of anhydrous ethanol, 100 mL of triethoxysilane solution containing Schiff base BD-TES, 2-3 g of diphenylsilanediol DPSD and 9-9.5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO were reacted at 70-90° C. for 5-7 h to obtain an organic phosphorus-silicon system flame retardant;

[0018] The structural formula of the BD-TES is:

[0019]

[0020] The present invention also provides a method for preparing the fiber-grade multi-component synergistic flame-retardant polyamide 6, comprising the following steps:

[0021] The multi-component synergistic flame retardant powder and polyamide 6 pellets are melt-blended and then sequentially extruded, cooled, pelletized and dried to obtain fiber-grade multi-component synergistic flame retardant polyamide 6.

[0022] Furthermore, the temperature of the melt blending is 180-230° C., and the time of the melt blending is 0.5-2 h.

[0023] Furthermore, the extrusion temperature is 200-255° C., the main machine speed is 6-10 rpm, and the feeder speed is 6-9 rpm.

[0024] Furthermore, the temperature of the first zone of the extrusion is 200-220°C, the temperature of the second zone is 200-230°C, the temperature of the third zone is 210-245°C, the temperature of the fourth zone is 235-255°C, and the temperature of the fifth zone is 225-255°C.

[0025] Furthermore, the drying temperature is 95-120° C., and the drying time is 1-2 hours.

[0026] Beneficial effects of the present invention:

[0027] (1) The fiber-grade multi-component synergistic flame-retardant polyamide 6 prepared by the present invention has a limiting oxygen index of more than 32%, a heat release rate of more than 45%, no flaming droplets are generated during the combustion process, and has obvious smoke suppression and flame retardant effects;

[0028] (2) The mechanical loss of the fiber-grade multi-component synergistic flame-retardant polyamide 6 prepared by the present invention is less than 10%, and a certain spinnability can be maintained;

[0029] (3) The raw materials of the present invention are simple and easy to obtain, the preparation method is simple, the process is short, the equipment requirements are low, and it is very easy to industrialize production. DETAILED DESCRIPTION

[0030] The present invention provides a fiber-grade multi-component synergistic flame-retardant polyamide 6, which is prepared from raw materials comprising the following parts by weight:

[0031] 9.3-14 parts of multi-component synergistic flame retardant powder;

[0032] Polyamide 6 pellets 86-90.7 parts;

[0033] The multi-component synergistic flame retardant powder comprises an organic phosphorus-silicon system flame retardant, dialuminum hypophosphite and lanthanum oxide powder.

[0034] In the present invention, the multi-component synergistic flame retardant powder is preferably 11.5 to 13.7 parts by weight, and more preferably 13.7 parts.

[0035] In the present invention, the polyamide 6 pellets are preferably 86.3 to 88.5 parts by weight, and more preferably 86.3 parts by weight.

[0036] In the present invention, the mass ratio of the organic phosphorus-silicon system flame retardant, dialuminum hypophosphite and lanthanum oxide powder is 1-5:8:0.3-1, preferably 3-5:8:0.5-0.7, and more preferably 5:8:0.7.

[0037] In the present invention, the structural formula of the organic phosphorus-silicon system flame retardant is:

[0038]

[0039] Among them, R1 is R2 is R3 is

[0040] In the present invention, the preparation method of the organic phosphorus-silicon system flame retardant comprises the following steps:

[0041] 200 mL of anhydrous ethanol, 100 mL of triethoxysilane solution containing Schiff base BD-TES, 2-3 g of diphenylsilanediol DPSD and 9-9.5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO were reacted at 70-90° C. for 5-7 h to obtain an organic phosphorus-silicon system flame retardant;

[0042] The structural formula of the BD-TES is:

[0043]

[0044] Preferably, 200 mL of anhydrous ethanol, 100 mL of triethoxysilane solution containing Schiff base BD-TES, 2.5 to 2.9 g of diphenylsilanediol DPSD and 9.1 to 9.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO are reacted at 75 to 85° C. for 5.5 to 6.5 hours to obtain an organic phosphorus-silicon system flame retardant.

[0045] Further preferably, 200 mL of anhydrous ethanol, 100 mL of triethoxysilane solution containing Schiff base BD-TES, 2.7 g of diphenylsilanediol DPSD and 9.2 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO are reacted at 80° C. for 6 hours to obtain an organic phosphorus-silicon system flame retardant.

[0046] In the present invention, the synthesis process of the preparation method of the organic phosphorus-silicon system flame retardant is:

[0047]

[0048] The present invention also provides a method for preparing the fiber-grade multi-component synergistic flame-retardant polyamide 6, comprising the following steps:

[0049] The multi-component synergistic flame retardant powder and polyamide 6 pellets are melt-blended and then sequentially extruded, cooled, pelletized and dried to obtain fiber-grade multi-component synergistic flame retardant polyamide 6.

[0050] In the present invention, the melt blending temperature is 180-230° C., preferably 185-225° C., and more preferably 190-220° C.; the melt blending time is 0.5-2 h, preferably 0.6-1.8 h, and more preferably 0.7-1.5 h.

[0051] In the present invention, the extrusion temperature is 200-255°C, preferably 205-253°C, and more preferably 208-250°C; the main engine speed is 6-10rpm, preferably 7-9rpm, and more preferably 8rpm; the feeder speed is 6-9rpm, preferably 6.5-8.5rpm, and more preferably 7-8rpm.

[0052] In the present invention, the temperature of the extruded zone is 200-220°C, the temperature of the second zone is 200-230°C, the temperature of the third zone is 210-245°C, the temperature of the fourth zone is 235-255°C, and the temperature of the fifth zone is 225-255°C. Preferably, the temperature of the extruded zone is 205-215°C, the temperature of the second zone is 205-225°C, the temperature of the third zone is 215-240°C, the temperature of the fourth zone is 238-253°C, and the temperature of the fifth zone is 230-253°C. More preferably, the temperature of the extruded zone is 208-212°C, the temperature of the second zone is 208-220°C, the temperature of the third zone is 220-235°C, the temperature of the fourth zone is 240-250°C, and the temperature of the fifth zone is 235-250°C.

[0053] In the present invention, the drying temperature is 95 to 120° C., preferably 98 to 115° C., and more preferably 5 to 110° C.; the drying time is 1 to 2 hours, preferably 1 to 1.5 hours, and more preferably 1 to 1.2 hours.

[0054] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0055] Example 1

[0056] A fiber-grade multi-component synergistic flame-retardant polyamide 6 is prepared from the following raw materials in parts by weight:

[0057] 5 parts of PBDSi powder, 8 parts of diethyl aluminum hypophosphite, 0.3 parts of lanthanum oxide, 86.7 parts of polyamide 6 pellets, the synthesis process of PBDSi powder is:

[0058]

[0059] PBDSi and diethylaluminum hypophosphite were mixed and then lanthanum oxide powder was added to obtain a multi-component synergistic flame retardant powder. The multi-component synergistic flame retardant powder and polyamide 6 pellets were melt-blended at 220°C for 0.5h, and then extruded in a twin-screw extruder. The temperature of zone one was set to 200°C, the temperature of zone two was set to 215°C, the temperature of zone three was set to 225°C, the temperature of zone four was set to 245°C, the temperature of zone five was set to 250°C, the main engine speed was set to 6rpm, and the feeder speed was set to 7rpm. After extrusion, it was cooled in a cooling water tank, pelletized by a pelletizer, and finally dried at 98°C for 1h to obtain a fiber-grade multi-component synergistic flame-retardant polyamide 6.

[0060] According to the test, compared with pure polyamide 6, the breaking strength of the fiber-grade multi-component synergistic flame-retardant polyamide 6 prepared in Example 1 decreased by 8.3%, and the breaking elongation decreased by 2.9%, and the spinnability was good.

[0061] Example 2

[0062] A fiber-grade multi-component synergistic flame-retardant polyamide 6 is prepared from the following raw materials in parts by weight:

[0063] 5 parts of PBDSi powder, 8 parts of diethyl aluminum hypophosphite, 0.5 parts of lanthanum oxide, 86.5 parts of polyamide 6 pellets. The synthesis process of PBDSi powder is the same as that of Example 1.

[0064] PBDSi and diethylaluminum hypophosphite are mixed and then lanthanum oxide powder is added to obtain a multi-component synergistic flame retardant powder. The multi-component synergistic flame retardant powder and polyamide 6 pellets are melt-blended at 220°C for 0.5h, and then extruded in a twin-screw extruder. The temperature of zone one is set to 210°C, the temperature of zone two is set to 220°C, the temperature of zone three is set to 220°C, the temperature of zone four is set to 240°C, the temperature of zone five is set to 255°C, the main engine speed is set to 7rpm, and the feeder speed is set to 7rpm; after extrusion, it is cooled in a cooling water tank, pelletized by a pelletizer, and finally dried at 100°C for 1.5h to obtain a fiber-grade multi-component synergistic flame-retardant polyamide 6.

[0065] The fiber-grade multi-component synergistic flame-retardant polyamide 6 prepared in Example 2 was tested for smoke suppression. The results showed that compared with pure polyamide 6, the fiber-grade multi-component synergistic flame-retardant polyamide 6 prepared in Example 2 showed a significant smoke suppression effect. The test results showed that with the increase in the amount of flame retardant added, the peak heat release rate (pHRR) of PA6 was further reduced to 800kW / m 2 , which is significantly reduced compared to PA6 without flame retardant. The total heat release (THR) is reduced to 25MJ / m 2 , compared with 40MJ / m without adding flame retardant 2 The peak smoke generation rate (SPR) is 0.20m2 / s, smoke density (Ds) is 45, oxygen index (LOI) is increased to 30%. The vertical burning grade reaches V-1, showing more obvious smoke suppression performance. The breaking strength decreases by 8.0%, the breaking elongation decreases by 3.1%, and the spinnability is good.

[0066] Example 3

[0067] A fiber-grade multi-component synergistic flame-retardant polyamide 6 is prepared from the following raw materials in parts by weight:

[0068] 5 parts of PBDSi powder, 8 parts of diethyl aluminum hypophosphite, 0.7 parts of lanthanum oxide, 86.3 parts of polyamide 6 pellets. The synthesis process of PBDSi powder is the same as that of Example 1.

[0069] PBDSi and diethylaluminum hypophosphite are mixed and then lanthanum oxide powder is added to obtain a multi-component synergistic flame retardant powder. The multi-component synergistic flame retardant powder and polyamide 6 pellets are melt-blended at 220°C for 1 hour, and then extruded in a twin-screw extruder. The temperature of zone one is set to 215°C, the temperature of zone two is set to 210°C, the temperature of zone three is set to 220°C, the temperature of zone four is set to 235°C, the temperature of zone five is set to 250°C, the main engine speed is set to 8rpm, and the feeder speed is set to 7rpm; after extrusion, it is cooled in a cooling water tank, pelletized by a pelletizer, and finally dried at 98°C for 1.7 hours to obtain a fiber-grade multi-component synergistic flame-retardant polyamide 6.

[0070] The test showed that compared with pure polyamide 6, the peak heat release rate (pHRR) of the fiber-grade multi-component synergistic flame-retardant polyamide 6 prepared in Example 3 was reduced to 400 kW / m 2 Compared with PA6 without flame retardant (1200kW / m 2 ) showed a significant inhibitory effect. The total heat release (THR) was reduced to 12MJ / m 2 , the peak smoke generation rate (SPR) is 0.08m 2 / s, the smoke density (Ds) is reduced to 20, and the oxygen index (LOI) is increased to 34%. The vertical combustion level reaches V-0, and there is no molten dripping, which proves the good anti-melting dripping property. During the combustion process, the material can effectively suppress the generation of smoke while maintaining low heat release and oxygen demand, showing excellent flame retardancy, anti-melting dripping and smoke suppression.

[0071] Example 4

[0072] A fiber-grade multi-component synergistic flame-retardant polyamide 6 is prepared from the following raw materials in parts by weight:

[0073] 5 parts of PBDSi powder, 8 parts of diethyl aluminum hypophosphite, 0.7 parts of lanthanum oxide, 90.3 parts of polyamide 6 pellets. The synthesis process of PBDSi powder is the same as that of Example 1.

[0074] PBDSi and diethylaluminum hypophosphite were mixed and then lanthanum oxide powder was added to obtain a multi-component synergistic flame retardant powder. The multi-component synergistic flame retardant powder and polyamide 6 pellets were melt-blended at 220°C for 1.5 hours and then extruded in a twin-screw extruder. The temperature of zone one was set to 205°C, the temperature of zone two was set to 215°C, the temperature of zone three was set to 235°C, the temperature of zone four was set to 235°C, the temperature of zone five was set to 250°C, the main engine speed was set to 7rpm, and the feeder speed was set to 7rpm. After extrusion, it was cooled in a cooling water tank, pelletized by a pelletizer, and finally dried at 105°C for 1 hour to obtain a fiber-grade multi-component synergistic flame-retardant polyamide 6.

[0075] After testing, compared with pure polyamide 6, the limiting oxygen index of the fiber-grade multi-synergistic flame-retardant polyamide 6 obtained in Example 4 can reach 28%, and the smoke density (Ds) is reduced from 80 to 25, which proves its lower smoke generation, heat release rate decreased by 40%, breaking strength decreased by 9.2%, and elongation at break decreased by 2.9%. It has good spinnability and good smoke suppression effect.

[0076] Example 5

[0077] A fiber-grade multi-component synergistic flame-retardant polyamide 6 is prepared from the following raw materials in parts by weight:

[0078] 5 parts of PBDSi powder, 8 parts of diethyl aluminum hypophosphite, 0.7 parts of lanthanum oxide, 88.3 parts of polyamide 6 pellets. The synthesis process of PBDSi powder is the same as that of Example 1.

[0079] PBDSi and diethylaluminum hypophosphite are mixed and then lanthanum oxide powder is added to obtain a multi-component synergistic flame retardant powder. The multi-component synergistic flame retardant powder and polyamide 6 pellets are melt-blended at 220°C for 1.5 hours, and then extruded in a twin-screw extruder. The temperature of zone one is set to 220°C, the temperature of zone two is set to 225°C, the temperature of zone three is set to 235°C, the temperature of zone four is set to 240°C, the temperature of zone five is set to 250°C, the main engine speed is set to 8rpm, and the feeder speed is set to 8rpm; after extrusion, it is cooled in a cooling water tank, pelletized by a pelletizer, and finally dried at 98°C for 1.8 hours to obtain a fiber-grade multi-component synergistic flame-retardant polyamide 6.

[0080] The test showed that compared with pure polyamide 6, the peak heat release rate (pHRR) of the fiber-grade multi-component synergistic flame-retardant polyamide 6 obtained in Example 5 was further reduced to 450 kW / m 2 , significantly better than other groups. The total heat release (THR) dropped to 15MJ / m2 , the peak smoke generation rate (SPR) is reduced to 0.10m 2 / s, smoke density (Ds) further reduced to 25. Oxygen index (LOI) reached 33%, and the vertical combustion grade was stable at V-0, without melt dripping, heat release rate decreased by 37%, breaking strength decreased by 9.7%, breaking elongation decreased by 2.9%, and spinnability was good.

[0081] Example 6

[0082] A fiber-grade multi-component synergistic flame-retardant polyamide 6 is prepared from the following raw materials in parts by weight:

[0083] 3 parts of PBDSi powder, 8 parts of diethyl aluminum hypophosphite, 1 part of lanthanum oxide, 88 parts of polyamide 6 pellets. The synthesis process of PBDSi powder is the same as that of Example 1.

[0084] PBDSi and diethylaluminum hypophosphite were mixed and then lanthanum oxide powder was added to obtain a multi-component synergistic flame retardant powder. The multi-component synergistic flame retardant powder and polyamide 6 pellets were melt-blended at 220°C for 1.5 hours and then extruded in a twin-screw extruder. The temperature of zone one was set to 220°C, the temperature of zone two was set to 225°C, the temperature of zone three was set to 230°C, the temperature of zone four was set to 240°C, the temperature of zone five was set to 255°C, the main engine speed was set to 9rpm, and the feeder speed was set to 9rpm. After extrusion, it was cooled in a cooling water tank, pelletized by a pelletizer, and finally dried at 98°C for 1.8 hours to obtain a fiber-grade multi-component synergistic flame-retardant polyamide 6.

[0085] After testing, the peak heat release rate (pHRR) of flame retardant polyamide 6 in Example 6 is 450 kW / m 2 Compared with PA6 without flame retardant (1200kW / m 2 ) is significantly reduced. The total heat release (THR) is also 40MJ / m 2 Reduced to 15MJ / m 2 , indicating that the heat released during combustion is greatly reduced. In addition, the peak smoke generation rate (SPR) is reduced to 0.15m 2 / s, while the PA6 without flame retardant is 0.45m 2 / s, and the smoke density (Ds) decreased from 80 to 25, further proving its lower smoke generation. The oxygen index (LOI) increased from 26.7% to 32%, the vertical burning grade increased from V-2 to V-0, and no melt dripping occurred during the combustion process. These results show that the flame retardant polyamide 6 obtained has good smoke suppression performance under fire conditions, can effectively reduce smoke and heat release, and improve safety. The breaking strength decreased by 8.5%, the breaking elongation decreased by 3%, and the spinnability was good.

[0086] It can be seen from the above embodiments that the present invention provides a fiber-grade multi-component synergistic flame-retardant polyamide 6 and a preparation method thereof. The method melt-blends a multi-component synergistic flame retardant solution with polyamide 6 pellets, and the obtained flame-retardant polyamide 6 is tested to show a limiting oxygen index of more than 34%, a heat release rate of more than 45%, and a total heat release (THR) of 12MJ / m 2 , the peak smoke generation rate (SPR) is 0.08m 2 / s, the smoke density (Ds) dropped to 20. During the combustion process, the material did not produce flaming droplets, showing an obvious flame retardant effect. The PA6 after melt blending was sequentially subjected to extrusion, cooling, pelletizing and drying processes to finally obtain fiber-grade multi-component synergistic flame retardant polyamide 6. The mechanical loss of the obtained product was less than 10%, and it could maintain certain spinnability. The flame retardant polyamide 6 finally obtained showed good flame retardancy, anti-droplet and smoke suppression.

[0087] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A fiber-grade multi-component synergistic flame-retardant polyamide 6, characterized in that: Prepared from the following raw materials in parts by weight: 9.3-14 parts of multi-component synergistic flame retardant powder; Polyamide 6 pellets 86-90.7 parts; The multi-component synergistic flame retardant powder comprises an organic phosphorus-silicon system flame retardant, dialuminum hypophosphite and lanthanum oxide powder.

2. The fiber-grade multi-component synergistic flame-retardant polyamide 6 according to claim 1, characterized in that: The mass ratio of the organic phosphorus-silicon system flame retardant, dialuminum hypophosphite and lanthanum oxide powder is 1-5:8:0.3-1.

3. The fiber-grade multi-component synergistic flame-retardant polyamide 6 according to claim 1 or 2, characterized in that: The structural formula of the organic phosphorus-silicon system flame retardant is: Among them, R1 is R2 is R3 is 4. The fiber-grade multi-component synergistic flame-retardant polyamide 6 according to claim 3, characterized in that: The preparation method of the organic phosphorus-silicon system flame retardant comprises the following steps: reacting 200 mL of anhydrous ethanol, 100 mL of a triethoxysilane solution containing a Schiff base BD-TES, 2 to 3 g of diphenylsilanediol DPSD and 9 to 9.5 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO at 70 to 90° C. for 5 to 7 hours to obtain the organic phosphorus-silicon system flame retardant; The structural formula of the BD-TES is:

5. A method for preparing the fiber-grade multi-component synergistic flame-retardant polyamide 6 according to any one of claims 1 to 4, characterized in that: The following steps are involved: The multi-component synergistic flame retardant powder and polyamide 6 pellets are melt-blended and then sequentially extruded, cooled, pelletized and dried to obtain fiber-grade multi-component synergistic flame retardant polyamide 6.

6. The preparation method according to claim 5, characterized in that: The temperature of the melt blending is 180-230° C., and the time of the melt blending is 0.5-2 h.

7. The preparation method according to claim 5 or 6, characterized in that: The extrusion temperature is 200-255° C., the main machine speed is 6-10 rpm, and the feeder speed is 6-9 rpm.

8. The preparation method according to claim 7, characterized in that: The temperature of the first zone of the extrusion is 200-220°C, the temperature of the second zone is 200-230°C, the temperature of the third zone is 210-245°C, the temperature of the fourth zone is 235-255°C, and the temperature of the fifth zone is 225-255°C.

9. The preparation method according to claim 8, characterized in that: The drying temperature is 95-120° C., and the drying time is 1-2 hours.

Citation Information

Patent Citations

  • A Schiff base PN-Si flame-retardant PA6, fiber and its preparation method

    CN110656394B

Cited By

  • Fiber-grade multi-element synergistic flame-retardant polyamide 6 and preparation method thereof

    CN117343536A